Perbedaan Komposisi Tubuh Wanita di 3 Wilayah (Baduy Luar, Salatiga, dan Kota Bambu) - Fadil Hidayat; Santoso, Alexander Halim; Wijaya, Bryan Anna (Pusat riset dan Inovasi Nasional, 2026)
This study aimed to analyze differences in body composition among adult women across three regions with distinct sociocultural and environmental characteristics: Baduy Luar (rural–traditional), Salatiga (semi-urban), and Kota Bambu (urban). Using a cross-sectional design, the study involved 268 participants and assessed total body fat, visceral fat, subcutaneous fat, and skeletal muscle mass using the OMRON HBF-370 analyzer. Significant differences were observed across most body composition parameters (p < 0.001). Women living in the urban area exhibited the highest levels of total fat, visceral fat, and subcutaneous fat, reflecting the influence of urbanization and sedentary lifestyle on adiposity. Conversely, women in the rural–traditional community demonstrated the highest skeletal muscle mass across all body regions, consistent with their physically demanding daily activities and traditional dietary patterns. These findings highlight the substantial role of environmental context in shaping metabolic health and cardiometabolic risk. Targeted public-health interventions—such as structured physical-activity promotion and nutrition education in urban populations, and preservation of active lifestyles in rural communities—are recommended. Longitudinal studies are warranted to clarify causal pathways and further characterize metabolic determinants.